Danish secondary schools 1880-1950: national legislative framework and local implementation - Christian Larsen (Taylor & Francis Group, 2018)
This article analyses and compares local people's and communities' strategies when implementing a national legislative framework in secondary schools in Denmark, 1880-1950, focusing particularly on the history of the school creation and survival process. For the purposes of this study, three different kinds of cities with secondary schools are examined: a traditional market town, a new provincial town, and a railway town. The article explains how headmasters and school managers in different education landscapes acted in these contexts and found a niche in the local education market amongst other local schools, thereby securing the existence of the school. In all three cases, the municipality played an important role in the survival of the venture school. However, it was also important to maintain a good relationship with the parents who provided the school with the pupils and the communities to which the school belonged.